DINASTI POLITIK MBAH SAITUN (Studi pada Kepala Desa Manduro Tahun 1990-2021 Kecamatan Kabuh Kabupaten Jombang) - Eliza Novita Sari; Mutmainnah Mutmainnah (Universitas Trunojoyo Madura, 2023)
This study aims to explain how the poitical dynasty of the descendants Mbah Saitun used Mbah Saitun’s charisma and cooperated with chroniclers called clientalism practices in order to gain power and position. This study uses the concept of Donald V. Kurtz’s thought, namely the theory of dynastic politics which was supported by the concept of clienttalism as the basis for analyzing data finding. Researchers used qualitative research method and case study approach. As well as in the process of collecting data using non-participant observation method and unstructured interview in order to obtain informations that were in accordance with the actual conditions. The results showed that there was an elite group in Manduro Vllage who controlled the Manduro Village government and was accupied by the descendants of Mbah Saitun who used the story of Mbah Saitun’s good image during his lifetime. In addition, the elite group cooperates with formal and informal figures, namely village officials and elders of Manduro Village to perpetuate the power of Mbah Saitun’s descendants.